Blockchain for information security and privacy - Rao, Udai Pratap (Boca Raton, FL : CRC Press, 2022)
Distributed and peer-to-peer (P2P) applications are increasing daily, and cyberattacks are constantly adopting new mechanisms to threaten the security and privacy of users in these Internet of Things (IoT) environments. Blockchain, a decentralized cryptographic-based technology, is a promising element for IoT security in manufacturing, finance, healthcare, supply chain, identity management, e-governance, defence, education, banking, and trading. Blockchain has the potential to secure IoT through repetition, changeless capacity, and encryption. Blockchain for Information Security and Privacy provides essential knowledge of blockchain usage in the mainstream areas of security, trust, and privacy in decentralized domains. This book is a source of technical information regarding blockchain-oriented software and applications. It provides tools to researchers and developers in both computing and software engineering to develop solutions and automated systems that can promote security, trust, and privacy in cyberspace. FEATURES Applying blockchain-based secured data management in confidential cyberdefense applications Securing online voting systems using blockchain Safeguarding electronic healthcare record (EHR) management using blockchain Impacting security and privacy in digital identity management Using blockchain-based security and privacy for smart contracts By providing an overview of blockchain technology application domains in IoT (e.g., vehicle web, power web, cloud internet, and edge computing), this book features side-by-side comparisons of modern methods toward secure and privacy-preserving blockchain technology. It also examines safety objectives, efficiency, limitations, computational complexity, and communication overhead of various applications using blockchain. This book also addresses the combination of blockchain and industrial IoT. It explores novel various-levels of information sharing systems.
1. Blockchain Impact in Education and SocietyS. Gomathi, Mukesh Soni, Utkarsh Nigam, Bhavna Bajpai, and Subrata Chowdhury2. Apply and Analyse Several Blockchain Techniques in IoT and Big Data SectorNikhil Ranjan, Sarvesh Kumar, and Aakanksha Jain3. Blockchain: Trends, Role and Future ProspectsPriya Swaminarayan, Abhishek Mehta, Nihal Parsania, and Khushi Solanki4. Cybersecurity and Privacy Issues of Blockchain TechnologyAyushi Dwivedi, Amarnath Mishra, and Debabrata Singh5. Robust Digital Medical Image Watermarking and Encryption Algorithms Using Blockchain over DWT Edge CoefficientParesh Rawat and Piyush Kumar Shukla6. Enhanced Privacy and Security of Voters Ídentity in Interplanetary File System Based E-Voting ProcessNarendra Kumar Dewangan and Preeti Chandrakar7. Blockchain-Enabled Secure Internet of Vehicles: A Solution Taxonomy, Architecture, and Future DirectionsMohd Zuhair, Pronaya Bhattacharya, Ashwin Verma, and Umesh Bodkhe8. Blockchain-Based Federated Cloud Environment: Issues and ChallengesAshwin Verma, Pronaya Bhattacharya, Umesh Bodkhe, Mohd Zuhair, and Ram Kishan Dewangan9. Blockchain-Based Secured Data Management in Confidential Cyber Defence ApplicationsS. Satheesh Kumar, S. Gokul Kumar, S. Chandraprabha, B. Maruthi Shankar, and S.A. Siva Kumar10. Blockchain Technology for Privacy and Security Issues and Challenges in IoT-Based SystemsC.J. Raman, S. Usha Kiruthika, L. Javid Ali, and S. Kanaga Suba Raja11. A Secure Online Voting System Using BlockchainMehak Wadhwani, Nisha Mansoori, Shivangi Tanwar, Aanchal Handa, and Bhavesh N. Gohil12. Secure Electronic Health Records (EHR) Management Using BlockchainAtharva Kalsekar, Avinash Jaiswal, Rogin Koshy, Sameer Mandloi, and Bhavesh N. Gohil13. Blockchain Impact of Security and Privacy in Digital Identity ManagementSmita Bansod and Lata L. Ragha14. A New Ecosystem for Digital Identity Verification Using BlockchainShubham Gupta, Kevin Shah, Aditya Hirapara, Deep Mistry, Ankur Bang, and Udai Pratap Rao15. Blockchain-Based Security and Privacy for Smart ContractsVivek Kumar Prasad, Chandan Trivedi, Dhaval Jha, and Madhuri Bhavsar16. Blockchain Application in Digital Identity Management in ElectionRajeev Kumar Gupta, Sweta Gupta, and Rajit Nair17. Leveraging Blockchain Technology for Decentralized Domain Name Broker ServiceSankita Patel, Ujjwal Kumar, Hrishabh Sharma, Amruta Mulay, and Rishabh Kumar18. Using Blockchain for Digital Copyrights ManagementNirmal Kumar Gupta, Anil Kumar Yadav, and Ashish Jain
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Information Technology; COMPUTERS / Security / General; COMPUTERS / Cryptography; Blockchains (Databases); Computer security